2015
DOI: 10.1016/j.nbd.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of fractalkine–CX3CR1 pathway in seizure-induced microglial activation, neurodegeneration, and neuroblast production in the adult rat brain

Abstract: Temporal lobe seizures lead to an acute inflammatory response in the brain primarily characterized by activation of parenchymal microglial cells. Simultaneously, degeneration of pyramidal cells and interneurons is evident together with a seizure-induced increase in the production of new neurons within the dentate gyrus of the hippocampus. We have previously shown a negative correlation between the acute seizure-induced inflammation and the survival of newborn hippocampal neurons. Here, we aimed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 57 publications
3
74
0
1
Order By: Relevance
“…Following seizures, changes in the morphological characteristics of microglia, such as increased numbers, increased cell body size, fewer processes, and decreased process branching have been reported [69]. In addition, increased expression of certain proteins, such as fractalkine receptors, have been observed in epileptic patients [79]. (Fractalkine receptors are selectively expressed on microglia and the fractalkine chemokine is expressed by neurons, facilitating a privileged interaction between the two populations [80]).…”
Section: Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…Following seizures, changes in the morphological characteristics of microglia, such as increased numbers, increased cell body size, fewer processes, and decreased process branching have been reported [69]. In addition, increased expression of certain proteins, such as fractalkine receptors, have been observed in epileptic patients [79]. (Fractalkine receptors are selectively expressed on microglia and the fractalkine chemokine is expressed by neurons, facilitating a privileged interaction between the two populations [80]).…”
Section: Microgliamentioning
confidence: 99%
“…On the other hand, there is evidence for a harmful neurodegenerative role for microglia in epilepsy. Ali et al, for example, found that the inhibition of fractalkine signaling reduced neurodegeneration in the hippocampus [79]. In addition, microglia may contribute to seizure-induced aberrant neurogenesis [84].…”
Section: Microgliamentioning
confidence: 99%
“…3,10,[34][35][36][37] For Ox-42 staining, images of ROIs were taken at 4× magnification with an AxioCam Erc5s (ZEISS, Germany) and converted into 8-bit images in ImageJ. ROI included the entire hippocampal cornu ammonis (CA)1, CA3, CA4, hilar sub-regions, and piriform cortex (PC).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…3 The cells were counted in 3 sections and the average number of cells per section was recorded. ROIs were delineated for each hippocampal subregion and piriform cortex.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation